Missed opportunities for screening congenital syphilis early during pregnancy: A case report and brief literature review - Peng, Lei-Wen; Gao, Yu-Jie; Cui, Ya-li; Xu, Huang; Gao, Zheng-Xiang (Frontiers in Public Health, 2023)
Congenital syphilis is a significant public health problem. Pregnant women infected with Treponema pallidum present with various clinical manifestations, mainly including skin or visceral manifestations. The extensive clinical manifestations of T. pallidum infection mimic those of many other diseases during pregnancy, which may lead to delayed diagnosis and serious consequences. We report a case of foetal T. pallidum infection and premature delivery in a pregnant woman. The pregnant woman presented with a suspected maculopapule, which is usually associated with secondary syphilis. Her syphilis screening was negative at 16 weeks of gestation. The dermatologists did not consider the possibility of T. pallidum infection. This case shows that even if the early syphilis screening of pregnant women is negative, they may still be infected with T. pallidum during pregnancy. Doctors should exclude the possibility of T. pallidum infection in patients with a rash with no obvious cause. The health status of patients’ spouses should be assessed during pregnancy. Additionally, perinatal health education is necessary for women and their spouses during pregnancy. The abovementioned factors could reduce the probability of T. pallidum infection in pregnant women and their infants.